2014
DOI: 10.2310/jim.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Feasible Timing of Elective Noncardiac Procedure after Antiplatelet Discontinuation in Patients Treated with Antiplatelet Agents

Abstract: The feasible timing of NCP after discontinuation of APAs showed less than 5 days. VerifyNow is useful in the evaluation of antiplatelet reversal after discontinuation of APAs. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…According to the 2014 American College of Cardiology/American Heart Association guideline, initiation or continuation of ASA is not helpful in patients undergoing elective noncardiac noncarotid operation, except in patients who have had previous coronary artery stent, unless the risk of ischemic insults is higher than that of postoperative hemorrhage 8). A recent study using platelet functional assays demonstrated that the mean time for complete reversal of platelet reactivity is 2.6 days in patients who take low-dose ASA and 2.8 days in those who take clopidogrel 9). The authors recommended that the appropriate time for noncardiac procedures after stopping antiplatelet agents be less than 5 days 9)…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2014 American College of Cardiology/American Heart Association guideline, initiation or continuation of ASA is not helpful in patients undergoing elective noncardiac noncarotid operation, except in patients who have had previous coronary artery stent, unless the risk of ischemic insults is higher than that of postoperative hemorrhage 8). A recent study using platelet functional assays demonstrated that the mean time for complete reversal of platelet reactivity is 2.6 days in patients who take low-dose ASA and 2.8 days in those who take clopidogrel 9). The authors recommended that the appropriate time for noncardiac procedures after stopping antiplatelet agents be less than 5 days 9)…”
Section: Discussionmentioning
confidence: 99%
“…Four veterinary studies (LOE 3, Fair) and 3 from human medicine (LOE 6, Good) provided evidence for this guideline. In patients receiving irreversible antiplatelet agents, a 24‐hour withdrawal time is unlikely to be different than not discontinuing the agent at all in patients at high risk for thrombosis and hence this guideline reflects as given in Section 5.2.…”
Section: Guidelinesmentioning
confidence: 96%
“…Furthermore, two complications such as difficult hemostasis [13] and postoperative intracranial hemorrhage [14] contributed to the poor outcome in the TBI patients. Therefore, it was recommended that all APT should be stopped more than 5 days prior to neurosurgical operation [15]. However, these patients required an urgent decompressive craniectomy, which cannot be delayed to the time when the effect of antiplatelet drugs on hemorrhagic complications disappears.…”
Section: Discussionmentioning
confidence: 99%